KUALITAS MAKANAN JAJANAN TEMPURA 01 SDN BOGEM I SUKOMORO-MAGETAN TAHUN 2014 - Ernawati .; Budi Yulianto; Lilis Prihastini (Poltekkes Kemenkes Surabaya, 2014)
Tempura is a kind of snack well liked by children because they are delicious and its inexpensive.Being so inexpensive there is always a possibility that some aspects of food quality are compromised. Thisresearch was intended to learn on the quality of tempura snacks on the basis of their physical, chemicaland microbiological aspects.This was considered as a descriptive research, focusing on the quality of tempura snacks sold byvendors in the vicinity of SON Bogem I, to be riviewed from physical aspects (color, smell, taste, andtexture), chemical (borax and formalin) and microbiological aspects (bacterial count). The population to bestudied were all tempura snacks sold by vendors in the vicinity of SON Bogem I. In this research 3 samplesof tempura snacks were taken. These samples were selected using simple random sampling. .The result indicated that the physical quality of all sample were poor. On inspection of chemicalquality all samples were positive for borax and formalin contents. Examination of the bacterial count onsamples tempura snacks resulted in a mean of sample 1 as 493.3 colonies/gram, sample 2 was 133.7colonies/gram and sample 3 was 560 colonies/gram. Therefore, according the quality standard desionatedin Surat Keputusan Kepala Badan POM RI No. HK.00.06.1.52.4011 Tahun 2009 Tentang Penetapan BatasCemaran Mikroba dan Kimla Oalam Makanan, that is 100,000 colonies/gram, this meant that sample 2exceeded the limit.This research concluded that based on their physical, chemical and microbiological aspects,tempura snacks sold by vendors in the vicinity of SON Bogem I, kecamatan Sukomoro kabupaten Magetanshould be disqualified for consumption. The study is warning the community to be more selective andtaking a good care in buying of snacks, specially of tempura snacks.